Nucleic Acid-based Cancer Therapy for Advanced-stage Solid Tumors: A Brief Overview - Mustafa, Mohd; Islam, Badar ul; Tantry, Irfan Qadir; Habib, Safia (Archives of Advances in Biosciences, 2024)
Introduction: The management of advanced-stage solid tumors remains a formidable challenge in oncology, often necessitating a combination of treatment modalities with limited efficacy. Nucleic acid-based drugs have emerged as promising therapeutic options, offering novel approaches to combat treatment-resistant tumors. This editorial review briefly analyzes viral and non-viral nucleic acid-based treatments for solid tumors, including their development, clinical activity, mechanisms of action, and prospects. Viral vectors, such as adenoviruses and lentiviruses, enable the delivery of therapeutic genes directly into tumor cells or the modulation of the tumor microenvironment, resulting in regulatory approvals for several gene therapies. Non-viral delivery systems, including lipid nanoparticles and polymer-based carriers, offer alternative strategies for transporting therapeutic nucleic acids into tumor cells, with precise drug release and targeting control. Materials and Methods: The literature review is based on searches of the PubMed database, Web of Science, Scopus, and Google Scholar using specific keywords. The article is based on manuscripts published between 2021 and 2024. Results: The mechanistic actions of nucleic acid-based drugs are diverse, encompassing direct tumor cell killing, modulation of the immune response, and inhibition of oncogenic pathways. Importantly, these therapeutic approaches demonstrate a favorable safety profile compared to traditional chemotherapy agents, minimizing off-target effects and reducing adverse events. The tumor microenvironment significantly influences the effectiveness of nucleic acid-based therapies, requiring strategies to improve drug delivery and overcome resistance mechanisms. Ongoing clinical trials, preclinical studies, and advancements in manufacturing and stability technologies are expected to drive the next generation of nucleic acid agents, ensuring widespread accessibility and clinical utility. Conclusion: Nucleic acid-based drugs represent a transformative approach to cancer therapy, potentially revolutionizing treatment outcomes and ushering in an era of precision medicine in oncology.